INSTITUTE OF PRESIDENCY IN MODERN POLITICAL SYSTEMS: CONSTITUTIONAL, LEGAL, STATUS-ROLE AND POWER-FUNCTIONAL CHARACTERISTICS - Москалюк, М. Ф. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article examines the constitutional-legal, status-role and power-functional characteristics of the institute of presidency. Particular attention is paid to the political analysis of the role and place of the presidency in contemporary political systems. The influence of the dominant factors on the specificity of the presidency institution in the context of its positioning in the power system of checks and balances was described. A comparative analysis of the political and legal norms of responsibility / irresponsibility of the president and procedural mechanisms of elimination and replacement of him from the post of the head of state were done. The election procedure and the basic requirements for the candidature for the president in the modern political practice were determined.